Optimality of Diagonalization of Multicarrier Multi-Hop Linear Non-Regenerative MIMO Relays - Rong, Yue; Hua, Y. (IEEE, 2010)
In this paper, a multicarrier multi-hop multiple-input multiple-output (MIMO) relay system is investigated. A linear non-regenerative strategy is applied at each relay node. We show that for Schur-concave objective functions, the optimal source precoding matrix, the optimal relay amplifying matrices and the optimal receiving matrix jointly diagonalize the multicarrier multi-hop MIMO relay channel. And for Schur-convex objectives, such joint diagonalization along with a rotation of the source precoding matrix is also shown to be optimal. Using the optimal structure of the source and relay matrices, the multi-hop relay design problem boils down to the issue of power loading among the resulting parallel multi-hop single-input single-output (SISO) relay channels. This paper provides additional details of the multicarrier version of some of our recent results.